Assembly of an FtsZ Mutant Deficient in GTPase Activity Has Implications for FtsZ Assembly and the Role of the Z Ring in Cell Division - Mukherjee, Amit (American Society for Microbiology, 2001)
FtsZ, the ancestral homologue of eukaryotic tubulins, assembles into the Z ring, which is required for cytokinesis in prokaryotic cells. Both FtsZ and tubulin have a GTPase activity associated with polymerization. Interestingly, the ftsZ2 mutant is viable, although the FtsZ2 mutant protein has dramatically reduced GTPase activity due to a glycine-for-aspartic acid substitution within the synergy loop. In this study, we have examined the properties of FtsZ2 and found that the reduced GTPase activity is not enhanced by DEAE-dextran-induced assembly, indicating it has a defective catalytic site. In the absence of DEAE-dextran, FtsZ2 fails to assemble unless supplemented with wild-type FtsZ. FtsZ has to be at or above the critical concentration for copolymerization to occur, indicating that FtsZ is nucleating the copolymers. The copolymers formed are relatively stable and appear to be stabilized by a GTP-cap. These results indicate that FtsZ2 cannot nucleate assembly in vitro, although it must in vivo. Furthermore, the stability of FtsZ-FtsZ2 copolymers argues that FtsZ2 polymers would be stable, suggesting that stable FtsZ polymers are able to support cell division.